2015
DOI: 10.3168/jds.2014-8957
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of capillary blood obtained by a minimally invasive lancet technique to detect subclinical ketosis in dairy cows by using 3 different electronic hand-held devices

Abstract: The objective of this study was to evaluate the suitability of capillary blood obtained by a minimally invasive lancet technique to detect subclinical ketosis in 49 prepartum and 191 postpartum Holstein-Friesian cows using 3 different electronic hand-held devices [FreeStyle Precision (FSP, Abbott), GlucoMen LX Plus (GLX, A. Menarini), NovaVet (NOV, Nova Biomedical)]. The β-hydroxybutyrate (BHBA) concentration in serum harvested from coccygeal blood samples was analyzed in a laboratory and used as a reference v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…The previously reported average inter-and intra-assay coefficients of variations for another handheld meter, the FreeStyle Precision device, were 7.2 and 7.9% for capillary blood from the skin of the exterior vulva (Kanz et al, 2015), and 5.8 and 5.7% for whole blood from a tail vessel (Iwersen et al, 2013). The measurements from capillary blood at the ear yielded similar average inter-and intra-assay coefficients of variation of 2.6 and 11.7%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The previously reported average inter-and intra-assay coefficients of variations for another handheld meter, the FreeStyle Precision device, were 7.2 and 7.9% for capillary blood from the skin of the exterior vulva (Kanz et al, 2015), and 5.8 and 5.7% for whole blood from a tail vessel (Iwersen et al, 2013). The measurements from capillary blood at the ear yielded similar average inter-and intra-assay coefficients of variation of 2.6 and 11.7%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…With this threshold, the results from ROC analyses for capillary blood were excellent; overall accuracies were AUROC ≥90% with a Se of 100% for all 3 sampling locations and a Sp of at least 93%. Kanz et al (2015) evaluated the use of different handheld meters for BHB testing in capillary blood obtained from the skin of the exterior vulva. For the FreeStyle Precision and the NovaVet device, similar ρ s = 83% and 73% with lower mean ± standard deviation BHB differences of 0.08 ± 0.19 mmol/L and −0.01 ± 0.43 mmol/L, respectively, were described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work from Mahrt et al (2014) showed that blood samples can be collected at any time of day for precise measurement of BHB concentration in continuously fed dairy cows; however, the jugular vein or coccygeal vessels should be used for blood collection because blood BHB concentrations in the mammary vein are quite a bit lower. Other European colleagues (Kanz et al, 2015;Süss et al, 2016) have found that capillary measurement of blood BHB concentrations using a lancet device in the skin of the exterior vulva or ear is an acceptable and minimally invasive method for classifying cows with hyperketonemia.…”
Section: Bloodmentioning
confidence: 99%
“…This is easily taken from the coccygealvessels using a 20 or 18G needle, although capillary blood obtained by the minimally invasive lancet puncture is also valid (Kanz and others 2015). In our experience, using just a needle in the coccygeal vein or artery can produce a stream of blood that stains the meter (remember that the strip has to be connected to the meter before the blood is applied), so to prevent this, we usually connect the needle to a small syringe and then carefully dispense a drop of blood onto the strip (Fig d).…”
Section: Quantifying or Estimating Metabolites In Biological Fluidsmentioning
confidence: 99%